2018
DOI: 10.3233/bmr-170969
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sit-to-stand and static standing balance ability between patients with total knee arthroplasty and elderly healthy subjects

Abstract: Patients who had total knee arthroplasty showed decreased sit-to-stand and static standing balance ability compared with the control group in the initial period after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The static balance is evaluated by a single leg stance test, while the dynamic balance is assessed by the time up-and-go test (TUG) [11,[13][14][15]. In addition, the balance of the body can be objectively evaluated with physiological profile assessment and digital or computerized platforms [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The static balance is evaluated by a single leg stance test, while the dynamic balance is assessed by the time up-and-go test (TUG) [11,[13][14][15]. In addition, the balance of the body can be objectively evaluated with physiological profile assessment and digital or computerized platforms [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Shin et al examined static ability balance of patients after TKA. The data revealed TKA patients had decreased in static balance compared with the control group (146). As mentioned earlier, it could be suggested that the maintaining standing balance with the single leg depended on the knee joint proprioception.…”
Section: Discussionmentioning
confidence: 62%